Comparison of Myometrial Invasion Depth Examination Methods in Endometrial Cancer - Savaş Özdemir; Ozan Doğan; Alp Koray Kinter; Özgür Akbayır; Fatih Şahin (IMR Press, 2024)
Background: Endometrial cancer (EC) is often presents in the postmenopausal period. Among the risk elements are obesity, early menarche, late menopause, unopposed estrogen exposure associated with nulliparity, diabetes, advanced age (>55 years), and tamoxifen use. Endometrial biopsy is the gold standard diagnostic method. The typical surgical process comprises a complete removal of the uterus, a bilateral salpingo-oophorectomy, and cytological examination of peritoneal washing. Invasion of the myometrium (MI) is intricately linked to lymph node metastasis, which is observed in approximately 20% of deep MI cases and in 5% of cases with superficial MI. Therefore, a comprehensive assessment of women with EC, especially those with MI, is important before treatment. The assessment for myometrial invasion (MI) and cervical stromal invasion often involves the use of transvaginal ultrasound (TVUS). The diagnostic accuracy of TVUS varies in reported studies, and some findings are comparable to those obtained through magnetic resonance imaging (MRI). The size of intraoperative tumors and MI is provided to surgeons by frozen section examination, offering crucial information. This study aimed to compare the preoperative TVUS and MRI findings, intraoperative frozen sections, and postoperative final results for 321 patients diagnosed with EC. Methods: Individuals who underwent surgery at the third-stage tertiary gynecologic-oncology clinic for EC were included in the study. The study excluded cases lacking preoperative biopsy, TVUS, and magnetic resonance imaging (MRI), as well as cases featuring obvious extrauterine lesions. Non-endometrioid cases, endometrial hyperplasia, and cases with an identification of organ involvement outside the uterus during surgery were also excluded. The TVUS and MRI findings were compared with the intraoperative frozen sections using McNemar's test. The concordance of the assessments was determined using the kappa coefficient. The statistical significance level, represented by alpha (α), was set at p < 0.05. Results: The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and kappa values for TVUS were 100%, 94.3%, 21.7%, 100%, and 0.34, respectively. For MRI, these values were 100%, 97.8%, 41.7%, 100%, and 0.579, and for frozen section, they were 100%, 99.7%, 83.3%, 100%, and 0.908, respectively. Conclusions: In addition to the gold standard frozen section, TVUS and MRI played an important preoperative role in determining the depth of invasion. While MRI is expensive, TVUS stands out for its practical nature and easy accessibility. In the preoperative examination, TVUS provided acceptable results in guiding intraoperative decisions for lymphadenectomy, with similar sensitivity to MRI and frozen sections.